Tuberculosis of the chest - Curvo-Semedo, L (2005)
The relationship between tuberculosis and mankind has been known for many centuries, with the disease being one of the major causes of illness and death. During the early 1980s, there was a widespread belief that the disease was being controlled, but by the mid-1980s, the number of cases increased. This change in the epidemiological picture has several causes, of which the AIDS epidemic, the progression of poverty in developing countries, the increase in the number of elderly people with an altered immune status and the emergence of multidrug-resistant tuberculosis are the most important. Mainly due to this epidemiological change, the radiological patterns of the disease are also being altered, with the classical distinction between primary and postprimary disease fading and atypical presentations in groups with an altered immune response being increasingly reported. Therefore, the radiologist must be able not only to recognize the classical features of primary and postprimary tuberculosis but also to be familiar with the atypical patterns found in immuno-compromised and elderly patients, since an early diagnosis is generally associated with a greater therapeutic efficacy. Radiologists are, in this way, presented with a new challenge at the beginning of this millennium.